2000
DOI: 10.1002/j.1551-8833.2000.tb09072.x
|View full text |Cite
|
Sign up to set email alerts
|

Giardia and Cryptosporidium Removals by clarification and filtration under challenge conditions

Abstract: This research examined removals of Giardia and Cryptosporidium by clarification (either dissolved‐air flotation [DAF] or plate sedimentation) and by dual‐media filtration following clarification. Studies were conducted for challenge conditions of cysts and oocysts (i.e., high influent concentrations) and for process design detention times and hydraulic loadings. To evaluate the effect of water temperature on performance, sets of experiments were performed for winter and spring seasons. DAF clarification perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
2
12
0
2
Order By: Relevance
“…Different types of particles have been proposed as potential surrogates (e.g., formalin-inactivated oocysts, heat-inactivated oocysts and latex microspheres) (Swertfeger et al, 1999;Edzwald et al, 2000;Emelko, 2003;Amburgey et al, 2005). However, few studies have actually compared the filtration behaviour of such surrogates with that of viable oocysts (Dai and Hozalski, 2003).…”
Section: Studies Of Cryptosporidium Filtration At the Laboratory-scalementioning
confidence: 99%
“…Different types of particles have been proposed as potential surrogates (e.g., formalin-inactivated oocysts, heat-inactivated oocysts and latex microspheres) (Swertfeger et al, 1999;Edzwald et al, 2000;Emelko, 2003;Amburgey et al, 2005). However, few studies have actually compared the filtration behaviour of such surrogates with that of viable oocysts (Dai and Hozalski, 2003).…”
Section: Studies Of Cryptosporidium Filtration At the Laboratory-scalementioning
confidence: 99%
“…Dugan et al (1999), using a conventional treatment pilot plant, observed oocyst removals of 4.1-5.2 log for runs in which finished water turbidity was maintained at < 0.3 ntu for 95% of the time. Edzwald et al (2000) obtained approximately 5-log removal of Giardia and Cryptosporidium in pilot-plant parasite challenge studies using dissolved-air flotation and filtration as well as settling plate sedimentation and filtration. Harrington et al (2001), using alum and conventional treatment in pilot-scale studies, observed an overall mean removal for oocysts of 1.6 log units and a removal of 1.9 log units for those runs in which the filter effluent had a turbidity of 0.2 ntu or less.…”
Section: © American Water Work Associationmentioning
confidence: 98%
“…Similarly, in pilot-plant challenge studies, Edzwald et al (2000) concluded that although particle-counting is an excellent tool for monitoring treatment to determine changes in performance, absolute particle numbers are not meaningful indicators of cyst or oocyst removal. In general, although high turbidity levels or particle counts indicate a greater potential for oocyst passage, low turbidity levels or particle counts do not provide absolute assurance of good oocyst removal.…”
Section: © American Water Work Associationmentioning
confidence: 99%
“…Pathogen removal through filtration has been studied extensively in the production of drinking water from surface water sources ( Amburgey et al, 2004 , 2005 ; Bustamante et al, 2001 ; Edzwald et al, 2000 ; Emelko et al, 2003 ; Harrington et al, 2003 ; Hsu and Huang, 2002 ; Logan et al, 2001 ; Nasser et al, 1995 ; Nieminski and Ongerth, 1995 ; Patania et al, 1995 ; Swertfeger et al, 1999 ; Xagoraraki et al, 2004 ). In potable water systems, it has been observed that removal of Giardia cysts and Cryptosporidium oocysts is influenced by the degree of filter maturation; use of coagulant chemicals ( Koivunen et al, 2003 ; Mosher and Hendricks, 1986 ; Patania et al, 1995 ); ionic strength; pH; zeta potential ( Bustamante et al, 2001 ; Hsu and Huang, 2002 ); and filter grain size ( Logan et al, 2001 ; Stevenson, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, under the Long‐Term 2 Enhanced Surface Water Treatment Rule enacted in 2006, at least 95% of the combined filter effluent turbidity measurements must be less than or equal to 0.15 NTU (40 CFR 141.727) ( U.S. EPA, 2003 ). While turbidity levels do not correspond to pathogen concentrations, the rule is based on conclusive evidence from a wide array of surface water filtration studies, which demonstrated that turbidity levels below 0.2 NTU are likely to correspond to low or nondetectable levels of Giardia and Cryptosporidium ( Edzwald et al, 2000 ; Emelko et al, 2005 ; Xagoraraki et al, 2004 ). In contrast, turbidity (or suspended solids) requirements for water reclamation facilities are based on monitoring of the disinfected effluent, with typical turbidity limits ranging from 2 to 5 NTU or suspended solids limits of 5 mg/L, depending on permit requirements ( U.S. EPA, 2004 ; York and Walker‐Coleman, 2000 ).…”
Section: Introductionmentioning
confidence: 99%